Tomato SlRbohB, a member of the NADPH oxidase family, is required for disease resistance against Botrytis cinerea and tolerance to drought stress - Li, Xiaohui; Zhang, Huijuan; Tian, Limei; Huang, Lei; Liu, Shixia; Li, Dayong; Song, Fengming (Frontiers in Plant Science, 2015)
NADPH oxidases (also known as respiratory burst oxidase homologues, Rbohs) are the enzymes that catalyze the generation of reactive oxygen species (ROS) in plants. In the present study, eight SlRboh genes were identified in tomato and their possible involvement in resistance to Botrytis cinerea and drought tolerance was examined. Expression of SlRbohs was induced by B. cinerea and Pseudomonas syringae pv. tomato but displayed distinct patterns. Virus-induced gene silencing (VIGS)-based silencing of SlRbohB resulted in reduced resistance to B. cinerea but silencing of each of other SlRbohs did not affect the resistance. The SlRbohB-silenced plants accumulated more ROS and attenuated expression of defense genes after infection of B. cinerea than the nonsilenced plants. Silencing of SlRbohB also suppressed flg22-induced ROS burst and the expression of SlLrr22, a marker gene related to PAMP-triggered immunity (PTI). Transient expression of SlRbohB in Nicotiana benthamiana led to enhanced resistance to B. cinerea. Furthermore, silencing of SlRbohB resulted in decreased drought tolerance, accelerated water loss in leaves and altered expression of drought-responsive genes. Our data demonstrate that SlRbohB positively regulates the resistance to B. cinerea, flg22-induced PTI and drought tolerance in tomato.